International Student Experiences and Graduate Employability: Perspectives and Issues (Comparative & International Education Series, 2022)
This chapter offers literature on international student experiences and their graduate employability in higher education as well as an overview of the book. It also highlights the socio-political environment that impacts international students’ employability and provides a holistic understanding of international student employability on a global scale, incorporating various higher education contexts, including the US, UK, Netherlands, Vietnam, and Japan. How to cite in APA: Zhao, X., Kung, M., Bista, K., & Ma, Y. (2022). International student experiences and graduate employability: Perspectives and issues. In X. Zhao, M. Kung, K. Bista, & Y. Ma (eds), Home and abroad: International student experiences and graduate employability (pp. 1-14). STAR Scholars. [order hardcopy ]